Compatibility of labelling gluten-free food products with current legal provisions based on the review of information on the labels - Mikołajczak, Natalia (Journal of Education, Health and Sport, 2018)
Introduction and aim: Gluten-free diet is a necessary diet in a treatment of gluten-dependent diseases. It means a complete exclusion from the menu of products being a source of gluten. An important issue in providing for consumers to choose the right gluten-free food product is the readability of information (about the presence of gluten in the product) and the ease of finding it on the packaging. The legal provisions on the labelling of this type of food require that the label be clearly and legibly formulated (e.g. gluten-free product) in a prominent place on the packaging, which should be helpful for people with celiac disease and gluten allergies to recognize the suitable products. The aim of the article was to evaluate the compatibility of labeling gluten-free food products with current legal provisions based on the review of information on the labels.Brief description of the state of knowledge: The research material was 125 labels of gluten-free products of various producers, which were available on the Masovian Voivodeship market (cereal and breakfast products (60), sugar and confectionery (35), fruit and vegetables products (8), meat and fish products (6), frozen products (4), drinks (2), other products (10)). The analysis included written and graphical information, which was found on the product label. 93 labels were characterized by the presence of 'gluten free product' in a vicinity of the product name. Very often, producers also placed a graphic sign in the form of a 'Crossed Ear' (98), also gave the license code next to the sign (93). On the cereal and breakfast products labels, manufacturers often placed additional written information to improve the product's credibility. Drinks were labelled only 'gluten-free products' (2), which is required by law.Summary: In accordance with the obligation in the regulations, most of the tested product labels met this requirement. Very popular formulation on the labels was a 'gluten-free product', and less often other specified in legal requirements. Only a small percentage of the analyzed product labels could raise doubts about the content of gluten and its safe consumption.